2003
DOI: 10.1002/bem.10105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a 902 MHz electromagnetic field emitted by mobile phones on human cognitive function: A replication study

Abstract: Our study was a replication and extension with methodological improvements to a previous study on effects of the electromagnetic field (EMF) emitted by a 902 MHz mobile phone on human cognitive functioning. Improvements on the previous study included multicentre testing and a double blind design. A total of 64 subjects (32 men and 32 women) in two independent laboratories performed a battery of 9 cognitive tasks twice: while the EMF was on and while it was off. Reaction times (RTs) and accuracy were recorded. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
130
5
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(151 citation statements)
references
References 12 publications
14
130
5
2
Order By: Relevance
“…While the present study's findings are consistent with early reports that exposure to PM RF affects working memory performance (Koivisto et al, 2000, Regel et al, 2007a, Regel et al, 2007b, the majority of the literature has not found such an influence (Haarala et al, 2003, Haarala et al, 2004, Haarala et al, 2007, Krause et al, 2007, Leung et al, 2011). Although we cannot be conclusive, a number of reasons related to the methodological improvements employed by this study may explain the results.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…While the present study's findings are consistent with early reports that exposure to PM RF affects working memory performance (Koivisto et al, 2000, Regel et al, 2007a, Regel et al, 2007b, the majority of the literature has not found such an influence (Haarala et al, 2003, Haarala et al, 2004, Haarala et al, 2007, Krause et al, 2007, Leung et al, 2011). Although we cannot be conclusive, a number of reasons related to the methodological improvements employed by this study may explain the results.…”
Section: Discussionsupporting
confidence: 91%
“…The majority of studies using this task, however, have not found any effects of PM RF exposure on performance (Haarala et al, 2003, Haarala et al, 2004, Haarala et al, 2007, Krause et al, 2007, Leung et al, 2011.…”
Section: Introductionmentioning
confidence: 93%
“…In particular, Preece et al [1999] and Koivisto et al [2000a,b] reported a shortening of the RT. Some work on verification of these reports failed to confirm their findings [Haarala et al, 2003.…”
Section: Discussionmentioning
confidence: 92%
“…In two replications and an extension study done by Haarala et al 2003Haarala et al , 2004 subjects in two different laboratories in Finland and Sweden performed doubleblind cognitive and short-term memory tasks. The phone was attached to the left side of the head.…”
Section: Introductionmentioning
confidence: 99%
“…In a replication and extension of Koivisto et al [2000a] with methodological improvements, Haarala et al [2003] had subjects perform a battery of nine cognitive tasks, including six tasks repeated from Koivisto et al [2000a] twice in two independent laboratories in Sweden and Finland. Improvements included a double blind study, multicenter testing with order of subjects counter balanced across subjects and gender, measurements of the SAR of the phones with the SPEAG's Dosimetric Assessment System 3 (DASY3, Schmid & Partner Engineering AG, Zurich, Switzerland), measurements of the temperature with a type K thermocouple sensor and a TES-1300 thermometer (TES Electrical Electronic Corp., Taipei, Taiwan), and statistical analyses performed using SPSS software (SPSS, Inc., Chicago, IL).…”
Section: Cognitive Studiesmentioning
confidence: 99%